You need to evaluate the critical numbers of the function and for this reason, you must differentiate the function with respect to t, using the product and chain rules, such that:

`g'(t) = (t*sqrt(4 - t))'`

`g'(t) = t'*sqrt(4 - t) + t*(sqrt(4 - t))'`

`g'(t) = sqrt(4 - t) + t*((4-t)')/(2sqrt(4 - t))`

`g'(t) = sqrt(4 - t) + (-t)/(2sqrt(4 - t))`

You need to solve for t the equation g'(t) = 0:

`sqrt(4 - t) + (-t)/(2sqrt(4 - t)) = 0`

`2(4 - t) - t = 0 => 8 - 2t - t = 0 => 3t = 8 => t = 8/3`

**Hence, evaluating the critical values of the given function, yields `t = 8/3.` **